Using translation concepts, it is found that the equation that represents the new function is:
The cube root parent function is given by:
![y = \sqrt[3]{x}](https://tex.z-dn.net/?f=y%20%3D%20%5Csqrt%5B3%5D%7Bx%7D)
<h3>Translation:</h3>
The function goes through these following translations:
- Vertically stretched by a factor of 3, that is, it is multiplied by 3, hence
.
- Reflected over the x-axis, that is, it is multiplied by -1, hence
.
- Translated 8 units down, that is, 8 is subtracted from the function, hence
.
Then, the equation is:
To learn more about translation concepts, you can take a look at brainly.com/question/13671886
Original Equation: 4x - 2(x+1) = 3x + 10
Step 1: Use Distributive Property
4x - 2x - 2 = 3x + 10
Step 2: Combine Like Terms
2x - 2 = 3x + 10
Step 3: Solve
2x - 2 = 3x + 10
- 2x -2x
--------------------------------
-2 = x + 10
-10 -10
------------------------
-12 = x
Answer:
3.50*3=10.5
the total will be $10.50
Step-by-step explanation:
Answer:
x=6
Step-by-step explanation:
ln 1=0
x-5=1
x=6
950 x 13 /100 x 120/365 = $ 40.60. Hope that's helpful.